2006
DOI: 10.1158/1078-0432.ccr-05-1761
|View full text |Cite
|
Sign up to set email alerts
|

Combination Chemotherapy and Radiation of Human Squamous Cell Carcinoma of the Head and Neck Augments CTL-Mediated Lysis

Abstract: Purpose: The combination of systemic multiagent chemotherapy (5-fluorouracil + cisplatin) and tumor irradiation is standard of care for head and neck squamous cell carcinoma (HNSCC). Furthermore, it has been shown that sublethal doses of radiation or chemotherapeutic drugs in diverse cancer types may alter the phenotype or biology of neoplastic cells, making them more susceptible to CTL-mediated cytotoxicity. However, little is known about the potential synergistic effect of drug plus radiation on CTL killing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 52 publications
(35 reference statements)
1
94
0
Order By: Relevance
“…Still another new paradigm to exploit in vaccine combination therapies is the phenomenon that certain standard of care therapeutics can actually alter the phenotype of tumor cells to render them more susceptible to T-cell -mediated lysis. This has been shown in a series of preclinical studies (48,49). Sublethal doses of radiation delivered via external beam have been shown to up-regulate tumor-associated antigens, fas, and/or adhesion molecules and/or down-regulate antiapoptotic genes, subsequently rendering these phenotypically altered tumor cells more susceptible to antigen-specific T-cell -mediated lysis.…”
Section: New Paradigms For Combinationtherapiesmentioning
confidence: 63%
See 1 more Smart Citation
“…Still another new paradigm to exploit in vaccine combination therapies is the phenomenon that certain standard of care therapeutics can actually alter the phenotype of tumor cells to render them more susceptible to T-cell -mediated lysis. This has been shown in a series of preclinical studies (48,49). Sublethal doses of radiation delivered via external beam have been shown to up-regulate tumor-associated antigens, fas, and/or adhesion molecules and/or down-regulate antiapoptotic genes, subsequently rendering these phenotypically altered tumor cells more susceptible to antigen-specific T-cell -mediated lysis.…”
Section: New Paradigms For Combinationtherapiesmentioning
confidence: 63%
“…Sublethal doses of radiation delivered via external beam have been shown to up-regulate tumor-associated antigens, fas, and/or adhesion molecules and/or down-regulate antiapoptotic genes, subsequently rendering these phenotypically altered tumor cells more susceptible to antigen-specific T-cell -mediated lysis. Chemotherapeutic agents, such as 5-fluorouracil (50), cisplatin, and gemcitabine (48), have also been used in sublethal doses inducing similar alterations of tumor cell phenotype and subsequent susceptibility to T-cell -mediated lysis. This may ultimately lead to another paradigm shift in vaccine combination therapies (i.e., when a patient does not respond to a drug or radiation therapy due to its lack of ability to lyse tumor cells, it may continue to be used with vaccine therapy due to its ability to augment vaccine-induced T-cell lysis of tumor).…”
Section: New Paradigms For Combinationtherapiesmentioning
confidence: 99%
“…Proinflammatory cytokines induced by radiation include interleukin 1β, tumor necrosis factor α and type 1 and 2 interferons (30,(33)(34)(35)(36). In addition, tumor cells that receive sublethal doses of radiation undergo phenotypic changes that enhance their susceptibility to immune effectors (37)(38)(39). Enhanced expression of death receptors (40,41), MHC class 1 molecules (37,42,43), costimulatory molecules (44), adhesion molecules (45)(46)(47), and stress-induced ligands (48-50) on tumor cells exposed to radiation increased their recognition and killing by T cells in vitro and/or in vivo in several cancer models.…”
Section: Radiation Response Of Tumors: the Role Of The Immune Systemmentioning
confidence: 99%
“…Although the results of this trial need confi rmation, a number of hypotheses can be off ered as to why active antigen-specifi c immunotherapy might show a favourable eff ect in patients treated with concurrent and not sequential chemoradiotherapy. Results of an in-vitro study using a head and neck model cell line 26 showed that cytotoxic T-cell mediated lysis directed against MUC1 was enhanced by previous treatment with concomitant chemoradiotherapy compared with either modality alone. Additionally, two studies by similar study teams 27,28 reported that some chemotherapeutic agents can induce immuno genic cell death whereas others induce tolero genic cell death.…”
Section: ·87 (0·75-1·00)mentioning
confidence: 99%